1934
DOI: 10.1144/gsl.jgs.1934.090.01-04.13
|View full text |Cite
|
Sign up to set email alerts
|

The Central and South-West Highland Epidiorites: A Study in Progressive Metamorphism

Abstract: I. Introduction Ever since the publication of Teall's description of the Scourie dyke (1885, p. 133) and its passage from a dolerite into a foliated amphibolite by the ordinary processes of metamorphism, petrologists have from time to time directed their researches along modern lines to a study of the metamorphism of basic igneous rocks. No formal review of the literature is necessary owing to the numerous references contained in the following pages, but among the earlier writers Macullo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

1947
1947
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(32 citation statements)
references
References 30 publications
3
29
0
Order By: Relevance
“…The progressive transformations found by Wiseman (1934) in metabasalt in .the Southwest Highlands are similar to those in the Riggins quadrangle. Hornblende low in aluminum and alkalis and high in calcium characterizes the biotite-zone rocks of the Scottish region; the hornblende changes progressively, and in the garnet zone it is higher in aluminum, iron : magnesium ratio, and alkalis, and lower in calcium than it is in the lower grade r'ocks.…”
Section: Comparison With Other Regionssupporting
confidence: 60%
See 1 more Smart Citation
“…The progressive transformations found by Wiseman (1934) in metabasalt in .the Southwest Highlands are similar to those in the Riggins quadrangle. Hornblende low in aluminum and alkalis and high in calcium characterizes the biotite-zone rocks of the Scottish region; the hornblende changes progressively, and in the garnet zone it is higher in aluminum, iron : magnesium ratio, and alkalis, and lower in calcium than it is in the lower grade r'ocks.…”
Section: Comparison With Other Regionssupporting
confidence: 60%
“…Chlorite does not persist far beyond the first appearance of biotite in metashales rich in aluminum and potassium; but the upper grade limit of chlorite in metaigneous rocks varies greatly from region to region. In northern Michigan (James, 1955(James, , p. 1467(James, -1473 and northern Manitoba (Ambrose, 1936), chlorite disappears midway between the biotite and garnet isograds in metaigneous rocks; in New Hampshire (Billings, 1956, p. 139) and the southwest Scottish Highlands (Wiseman, 1934), chlorite is stable up to about the garnet isograd; and in South Island; New Zealand (Reed, 1958) and in western Idaho (this report), chlorite is stable in rocks containing both garnet and oligoclase.…”
Section: Comparison With Other Regionsmentioning
confidence: 99%
“…This bluish-green amphibole is not characteristically developed in zones of contact alteration around granite intrusions; it is commonly, however, the characteristic amphibole in the epidiorites and amphibolites of migmatite areas. Furthermore, the Cornish epidiorites are closely similar to those found within the Dalradians, where the minerals of such rocks are regarded as indicating the grade of regional metamorphism, Wiseman (1934) having shown that the FeO/MgO ratio in the amphibole increases in the higher grades. The FeO/MgO ratios in the Cornish amphibolites are even higher than those recorded by Wiseman.…”
supporting
confidence: 56%
“…Studies of the metamorphism of basic igneous rocks in the Dalradian were also made in Cambridge (Phillips, 1930;Wiseman, 1934), complementing what was already known about the progressive metamorphism of pelitic rocks. Also of the Cambridge ‗school' was J.F.N.…”
Section: History Of Researchmentioning
confidence: 99%